AGROFORESTRY MANAGEMENT IN NIGERIA AND THE FEDERAL GOVERNMENT INTERVENTION ARTICLE BY RAINBOW STAR JOURNAL, LAGOS, NIGERIA - BALOGUN, KEHINDE OSENI (Global Journal of Food and Agribusiness Management, 2021)
In the course of the article the researcher discovered that the implications of the Federal Government of Nigeria’s intervention policy on forest and agroforestry system has not been fully realized by the farmers as it were. However, integrated land-use planning provides an essential strategic framework for balancing land uses. Moreso, such planning processes must be participatory, because it is farmers and other stakeholders who must finally put the plans into practice, and will do so only if they meet their needs and interests.